Response of four cultivars of cassava (Manihot esculenta Crantz) plantlets free of cassava mosaic virus to micropropagation in different media - YANDIA, Simplice Prosper; GANDONOU, GBOSSÈGNON CHRISTOPHE BERNARD (My University, 2018)
The aim of this study was to identify the best medium for the micropropagation of four cultivars (Sixmois, M61/061, Yalipe and Rendre) of cassava (Manihot esculenta, Crantz) plantlets free of mosaic virus. The effect of media on the morphogenesis in vitro was studied using different growth regulators combinations, added to MS medium, M0: MS without growth regulator; M1: MS+NAA (0.02 mg/l) ; M2 : MS+BAP (0.05 mg/l); M3: MS+NAA (0.02 mg/l) + BAP (0.05 mg/l); M4: MS+NAA (0.02 mg/l) + BAP (0.05 mg/l) + GA3 (0.02 mg/l). The percentage of bud enlargement was determined after one week; while plantlets height, number of nodes, number of leaves, number of roots and Roots length were determined after eight weeks. The results show that the percentage of bud enlargement ranged from 78 to 100% in all the mediums, M1 and M3 induced the highest percentages of bud induction. The highest plantlet was observed in the medium M4 with cultivar Yalipe (5.28 cm), whereas the weakest was observed in the medium M1 with cultivar M61.033 (1.68 cm). The highest number of nodes was observed in the medium M4 with cultivar M61/033 (2.73), whereas the weakest was observed in M4 with cultivar Rendre (1.26). The highest number of leaves was obtained in M4 with cultivar M61/033 (4.74), whereas the weakest was observed in M3 with cultivar Six-mois (2.00). Medium M1 induced the highest number of roots (3.47) with cultivar Yalipe, whereas the weakest was observed in M2 with M61/033 (0.10). The highest root length was observed in the medium, M1 with cultivar Rendre (4.72 cm), whereas the weakest was observed in M0 with cultivar M61/033 (1.68 cm).
Keywords: Cassava; morphogenesis in vitro; plant acclimatization; growth regulators